Management of Patella Fracture by Tension Band Wire Fixation - Muhammad Azeem Akhund, Kishore Kumar, Allah Nawaz Abbasi, Muhammad Faisal Shaikh, Karam All Shah , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To analysis the out come of patella fracture with tension band wiring fixation regarding its anatomical restoration, union time and functional outcome. Study Setting& Duration: This Quasi experimental study was designed and conducted in Department of Orthopaedic Surgery of Peoples University of Medical health & sciences Nawabshah (SBA), from January 2015 to July 2016. Methods: 30 patients having patella fracture were included and divided in two groups. Group A was stabilized with Modified tension band (MTB) fixationand group B for Lotke longitudinal anterior band (LAB) wiring techniques; each group consisted of 15 patients. Results: Total 30 patients were evaluated in this study equally divided into two . The mean age was 41+5.23 years. Range(20-70) years. 22(73.33%) were male patients and 8(26.66%) were females, with male to female ratio of 2.7:1, 12 cases (80%) achieve union in MTB group while only 7 (46.6%) cases achieve union in LAB group at 6-9 weeks with statistically significant p- value — 0.001. The mean healing time in MTB group was 7.3+ 3.1 weeks while in LAB group it was 9.1+ 2.1 weeks.Functional outcome was excellent in 53.33% patients of MTB group and 40% patients of LAB group, good was seen 26.66% patients in each group, fair in 13.33% patients of MTB group and 20% patients of LAB group and poor was in 6.66% (one) patient in MTB group and 26.66% (four) patients in LAB group. Conclusion: The modified tension band are more predictable as compare to that of longitudinal anterior band (LAB) in treatment of displaced transverse closed fractures of patella regarding anatomical restoration and functional outcome.